Optimalisasi Administrasi Personalia untuk Meningkatkan Kualitas Lembaga Pendidikan Islam - Azka As Sajidah; Ahmad Zainuri; Salsa Anindya (Politeknik Kampar, 2025)
The development of digital technology and artificial intelligence (AI) has brought significant transformations in various aspects of life, including the character formation of Generation Z. This research aims to explore the role of AI as a